The catalytic mechanism, metal dependence, substrate specificity, and biodiversity of ribonuclease H - Pang, Jing; Guo, Qinyu; Lu, Zheng (Frontiers in Microbiology, 2022)
Ribonucleoside monophosphates are inevitably incorporated into the DNA genome inside cells, and they need to be excised to avoid chromosome instability. Ribonucleases H (RNases H) are enzymes that specifically hydrolyze the RNA moiety from DNA and therefore are required for DNA integrity. Extensive studies have drawn a mostly clear picture of the mechanisms of RNase H catalysis, but some questions are still lacking definitive answers. This review summarizes three alternative models of RNase H catalysis. The two-metal model is prevalent, but a three-metal model suggests the involvement of a third cation in catalysis. Apparently the mechanisms underlying metal-dependent hydrolyzation are more complicated than initially thought. We also discuss the metal choices of RNases H and analyze how chemically similar cations function differently. Substrate and cleavage-site specificities vary among RNases H, and this is explicated in detail. An intriguing phenomenon is that organisms have diverse RNase H combinations, which may provide important hints to how rnh genes were transferred during evolution. Whether RNase H is essential for cellular growth, a key question in the study of in vivo functions, is also discussed. This article may aid in understanding the mechanisms underlying RNase H and in developing potentially promising applications of it.